Modern English Dictionaries. A Foreign User’s View - Karpova, Olga (Respectus Philologicus, 2019)
The article is devoted to the description of new trends in theory and dictionary making process of modern English lexicography. At the same time the paper also covers the main historic steps of formation and development of national English lexicography with special reference to the most reliable English dictionaries for general purposes (early glossaries and concordances, Samuel Johnson’s Dictionary, Oxford English Dictionary, etc.) and special purposes (English writers’ glossaries, concordances, lexicons to the complete and separate works of Chaucer, Shakespeare, and other famous English men of letters). The main accent is made on the digital époque of English national lexicography, describing innovative features of both printed and Internet dictionaries of various types and formats from the point of view of a user studying English as a foreign language. The paper touches upon new branches of English lexicography (collaborative, volunteer) with users’ needs and demands at the centre of dictionary making process.